1999
DOI: 10.1111/j.1469-8749.1999.tb00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning in children with typical cri du chat (5p–) syndrome

Abstract: This study is the first attempt to assess systematically the cognitive functioning in children diagnosed with typical cri du chat syndrome (CDCS) using neuropsychological test measures. Twenty‐six children aged between 6 years 4 months and 15 years 5 months (mean 8 years 3 months) completed a battery of tasks measuring IQ level, receptive and expressive language skills, and articulation. Twenty‐four children were in the severe learning‐disability range with no specific verbal or performance profile. Using more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 12 publications
2
30
0
2
Order By: Relevance
“…The findings also demonstrated that the use of eye contact in CdLS was far more fleeting during these points of high social demand in comparison to individuals with CdCS. Given that communicative ability is thought to be comparable between the two participant groups (Cornish & Munir, 1988;Cornish et al, 1999) it is assumed that any differences in communication between the groups are not attributable simply to communication impairment, but rather reflect group differences in response to social demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings also demonstrated that the use of eye contact in CdLS was far more fleeting during these points of high social demand in comparison to individuals with CdCS. Given that communicative ability is thought to be comparable between the two participant groups (Cornish & Munir, 1988;Cornish et al, 1999) it is assumed that any differences in communication between the groups are not attributable simply to communication impairment, but rather reflect group differences in response to social demand.…”
Section: Discussionmentioning
confidence: 99%
“…CdCS is caused by a deletion on the short arm of chromosome 5 (5p15; Goodhart et al, 1994;Overhauser et al, 1994) and occurs in approximately 1 in 50,000 births. Individuals with CdCS have similar levels of intellectual disability, expressive and receptive communication to those identified in CdLS (Cornish & Munir, 1988;Cornish, Bramble, Munir & Pigram, 1999). In contrast to individuals with CdLS, nonverbal communication skills and social interaction skills are reported to be a relative strength in CdCS (Cornish & Pigram, 1996;Cornish, Munir & Bramble, 1998;Sarimski, 2002) although, as is the case in CdLS, speech is compromised.…”
Section: Introductionmentioning
confidence: 93%
“…Invariably, receptive language and comprehension is remarkably better than expressive language (16). Regarding the social profile, many of the children with CdCS live at home and interact with society, eventually achieving communication and coordination improvements (15,17) being able to express their needs, establishing relationships with other people and developing different levels of motor activity (4,18). In contrast, there are studies that suggested limited communication improvements in which a great level of individual variability is shown (17).…”
Section: Behavior Language and Social Profilementioning
confidence: 99%
“…More recent, albeit limited, research data indicate that there is a wider range of cognitive ability (Cornish, 1996;Cornish, Bramble, Munir & Pigram, 1999). Progression in motor development is delayed and adaptive behaviour within the domains of socialisation, communication, daily living skills and motor skills does not appear to show any significant strengths or weakness, although no contrast groups have been employed in research studies (Cornish, Munir & Bramble, 1998).…”
Section: Intellectual Disabilitymentioning
confidence: 99%
“…Most individuals with CdCS have minimal or no speech (Cornish et al, 1999) while receptive language tends to be significantly more developed than expressive and written skills. According to Sohner and Mitchell (1991) indicators of compromised expressive communication are present prior to speech development and can be evidenced by a delayed pattern of babbling development during infancy.…”
Section: Communicationmentioning
confidence: 99%